Development of Digital Interactive Module “E-MOSI” (Elektronik Modul Puisi) for Grade IV Students of Elementary School of Kemala Bhayangkari 02 - Lily Nafilatul Maulidiana; Andarini Permata Cahyaningtyas; Yulina Ismiyanti (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
This study aims to develop electronic module teaching materials for fourth-grade poetry and determine their feasibility and practicality. This research is motivated by the difficulty of understanding Indonesian subjects, especially poetry materials, and the lack of alternative teaching materials. The novelty of this teaching material is in the form of modules that can be accessed utilizing gadgets and laptops, as well as the completeness of materials supported by audio and video learning. This type of research is development research, using the research and development method, consisting of ten development steps (potentials and problems, collecting data, product design, design validation, design revision, product trial, product revision, usage trial, product revision, and mass production. Based on these ten steps, the development of the digital interactive module "E-MOSI" (Elektronik Modul Puisi) or Electronic Poetry Module resulted in feasibility by the three validators, namely 85.7% with very feasible criteria. The percentage of practicality for small group trials was 86% of teacher responses and 94% of student responses, while large group trials resulted in teacher responses of 92% and student responses of 87.8%. The test results were also calculated using the t-test, with ha results being accepted, i.e., there were differences before and after using "E-MOSI". This study concludes that the development of the digital interactive module "E-MOSI" for fourth-grade students of SD Kemala Bhayangkari 02 met the very feasibility criteria and high practicality category.